2011
DOI: 10.1007/s00259-011-1843-8
|View full text |Cite
|
Sign up to set email alerts
|

123I-MIBG scintigraphy/SPECT versus 18F-FDG PET in paediatric neuroblastoma

Abstract: (123)I-MIBG scintigraphy and (18)F-FDG PET showed noticeable differences in their uptake patterns. (18)F-FDG PET was more sensitive and specific for the detection of neuroblastoma lesions. Our findings suggest that a (18)F-FDG PET scan may be useful in the event of discrepant or inconclusive findings on (123)I-MIBG scintigraphy/SPECT and morphological imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 24 publications
2
37
0
7
Order By: Relevance
“…In another study 123 I-MIBG scintigraphy and (18) F-FDG PET showed noticeable differences in their uptake patterns. 18 F-FDG PET was more sensitive and specific for the detection of neuroblastoma lesions [13] .…”
Section: Resultsmentioning
confidence: 95%
“…In another study 123 I-MIBG scintigraphy and (18) F-FDG PET showed noticeable differences in their uptake patterns. 18 F-FDG PET was more sensitive and specific for the detection of neuroblastoma lesions [13] .…”
Section: Resultsmentioning
confidence: 95%
“…Also, bone and bone marrow lesions could be masked or falsely interpreted as positive in patients receiving granulocyte colony-stimulating factor. In another study comparing 123 I-MIBG scintigraphy/SPECT and 18 F-FDG PET scan in pediatric neuroblastomas [ 57 ], the sensitivities were 50 and 78 % and the specifi cities were 75 and 92 %, respectively. The combined use of both modalities increased the sensitivity to 85 %.…”
Section: Imaging Featuresmentioning
confidence: 96%
“…The role and timing of, for example, 18 They found a sensitivity of 50% with 123 I-mIBG versus 78% with 18 F-FDG PET and a specificity of 75% with 123 I-mIBG and 92% with 18 F-FDG PET. They concluded that 18 F-FDG PET may be a valuable imaging modality for patients with discrepant or inconclusive findings on 123 I-mIBG single photon emission CT/scintigraphy [39]. Sharp et al retrospectively compared 113 paired 123 I-mIBG and 18 F-FDG PET scans at diagnosis.…”
Section: Challenge 5 Disease Assessment and Response Assessmentmentioning
confidence: 98%